Genetic regulation of allolysis in response to sub-lethal antibiotic stress in Streptococcus pneumoniae - MANISHA DASH; HIRAK R. DASH; SURAJIT DAS (Nusantara Bioscience, 2014)
Abstract. Dash M, Dash HR, Das S. 2014. Genetic regulation of allolysis in response to sub-lethal antibiotic stress in Streptococcus pneumoniae. Nusantara Bioscience 6: 111-117. Allolysis is the phenomenon of cell lysis induced by other cells of the same species. Gram-positive bacterium Streptococcus pneumoniae, a major human pathogen exhibits competence induced allolysis that increases the genetic recombination and enhances the virulence. During allolysis, a group of non-competent bacterial cells is lysed by another group of competent cells in the same culture. This process is regulated by com operon as well as bacteriocin. In this study, allolysis was induced in Streptococcus pneumoniae MTCC655 by sub-lethal dose of antibiotic (chloramphenicol) and the mechanism of allolysis has been deduced by amplification of lytA, lytC and cbpD genes in the bacterium. The strain was found to be resistant to a number of antibiotics including amoxicillin, cefpodoxime, erythromycin, and vancomycin. The early onset of allolysis induction from 7-9 h under normal conditions to 2-3 h by sub-lethal dose of chloramphenicol was observed.